Elevated-temperature creep of high-entropy alloys via nanoindentation. (November 2019) - Lin, P.H.; Chou, H.S.; Huang, J.C.; Chuang, W.S.; Jang, J.S.C.; Nieh, T.G.
Abstract: Abstract : High-entropy alloys (HEAs) have been the focus of wide-ranging studies for their applications as next-generation structural materials. For high-temperature industrial applications, creep behavior of structural materials is critical. In addition to high-temperature tensile, compressive, and notched tests, elevated-temperature nanoindentation is a relatively new testing method for HEAs. With the high accuracy of depth-sensing technology and a stable temperature-controlling stage, elevated-temperature time-dependent mechanical behavior of HEAs can be investigated, especially at localized regions without the limitations of the standard specimen size used for traditional creep testing. Also, the creep response from each grain in polycrystalline samples with various crystalline orientations can be explored in detail. This article overviews current progress in studying creep behavior in HEAs via nanoindentation technology.